Toxicological Effects of Tributyltin in Zebrafish (Danio rerio) Embryos - Kumudu Bandara R.V.; Pathmalal Manage M. (Environment and Natural Resources Journal, 2022)
Tributyltin (TBT) is known as an endocrine-disrupting chemical abundant in the aquatic environment. In the present study, zebrafish fish embryos were used to observe the chronic toxicity of TBT. Fish embryo toxicity analysis was carried out for different TBT concentrations (100, 50, 25, 12.5, 6.2, and 3.1 ng/L) and fertilized eggs were used to test each concentration effect. Fertilized eggs in 24-well plates (20 eggs in each well) were incubated at 26°C for four days and embryo coagulation, heartbeat of the embryo and mortality lethal endpoints (LC50 values) were recorded after 8, 24, 48, and 96 h. The results revealed that 100% coagulations of the embryos occurred at TBT doses of 50 and 100 ng/L. The coagulation significantly increased in a dose-dependent manner and TBT might induce coagulation of zebrafish embryos. Heartbeat changes were significantly decreased (p<0.05) in a dose-dependent manner at different TBT doses. LC50 values of TBT for zebrafish embryos were 19.9, 11.7, 7.3, and 5.2 ng/L at 8, 24, 48, and 96 h, respectively. The percentage of mortality was higher in embryos for the trace level of TBT, indicating that embryos are more sensitive to TBT toxicity. Hence, TBT is highly toxic and leads to a lethal effect on the zebrafish embryo, resulting in species extinction and declining biodiversity in the aquatic environment.